Optimized calibration of cryogenic silicon thermodiodes - Ivashchenko, O.M.; Shwarts, Yu.M.; Shwarts, M.M.; Kopko, D.P.; Sypko, M.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Shown in this paper is the efficiency of smoothing cubic spline approximation aimed at optimization of calibration of cryogenic silicon diode thermometers (SDTs). The proposed algorithm allows to significantly reduce time and material costs associated with calibration of SDTs.